New directions for research in foreign language education - Coffey, Simon; Wingate, Ursula (New York Routledge, Taylor & Francis Group, 2018)
New Directions for Research in Foreign Language Education brings together contributions by reputed scholars that examine the challenges, opportunities, and benefits of teaching and learning foreign languages. With a particular focus on languages other than English, the book looks at the socio-political dimension of language learning and teaching and the need to re-theorize multilingualism for our age. The volume includes a range of perspectives, from language teaching as an act of reconciliation to language learning across the lifespan, from innovations in assessment and curriculum to critical appraisals of pedagogy and textbook materials. Each chapter presents a clear case study drawn from diverse contexts to illustrate the different concerns of the contributors. The book is a valuable resource for all students, teachers, teacher educators and researchers who share an interest in researching multilingualism and the different facets of teaching and learning foreign languages.
Navigating precarious territory: teaching Turkish in Greek-Cypriot classrooms / Panayiota Charalambous, Constadina Charalambous and Ben Rampton -- Language learning as opportunity across the life span / Simon Coffey -- Foreign language teaching for citizenship development / Mairin Hennebry -- Not English but English-within-multilingualism / Jennifer Jenkins -- Glocal languages: the "globalness" and the "localness" of world languages / Manuela Guilherme -- L2 learning outside the classroom: new directions for research on intercultural interactions during study abroad / Rachel Shively -- French language textbooks as ideologically imbued cultural artefacts: political economy, neoliberalism and (self) branding / David Block and John Gray -- The need for new directions in modern foreign language teaching at english secondary schools / Ursula Wingate and Nick Andon -- Developing competence for French as a foreign language within a plurilingual paradigm / Nathalie Auger -- Assessing the diverse linguistic and cultural repertoires of students of diverse languages / Angela Scarino -- Embedding the assessment into the learning: a new direction for high-stakes speaking assessments / Martin East -- Toward an educational policy for U.S. collegiate foreign language instruction: Curricular considerations / Heidi Byrnes.
Includes bibliographical references and index.
Keywords: Second language acquisition; Language and languages -- Study and teaching